Characterising a microsatellite for DRB typing in Aotus vociferans and Aotus nancymaae (Platyrrhini) (2014)
Non-human primates belonging to the Aotus genus have been shown to be excellent experimental models for evaluating drugs and vaccine candidates against malaria and other human diseases. The immune system of this animal model must be characterised to assess whether the results obtained here can be extrapolated to humans. Class I and II major histocompatibility complex (MHC) proteins are amongst the most important molecules involved in response to pathogens; in spite of this, the techniques available for genotyping these molecules are usually expensive and/or time-consuming. Previous studies have reported MHC-DRB class II gene typing by microsatellite in Old World primates and humans, showing that such technique provides a fast, reliable and effective alternative to the commonly used ones. Based on this information, a microsatellite present in MHC-DRB intron 2 and its evolutionary patterns were identified in two Aotus species (A. vociferans and A. nancymaae ), as well as its potential for genotyping class II MHC-DRB in these primates. © 2014 López et al.